ANALISIS FINANSIAL PUPUK ORGANIK CAIR KELOMPOK TANI HUTAN KEMASYARAKATAN HARAPAN MAJU DI DESA MOBUI SEBAGAI UPAYA PENGEMBANGAN USAHA PERHUTANAN SOSIAL - Dian Charity Hidayat; Retno Maryani; Setiasih Irawanti; Mochammad Lutfi Susanto; Joko Ridho Witono (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2020)
Community Forest (CF) is a sustainable forest management scheme that involves local community in order to increase the level of community welfare. It is necessary to develop several business activities that are able to support forest ecology and improve the living standard of the community. These activities include making organic liquid fertilizer (POC). The purpose of this research is to analyze the business feasibility and business continuity of POC of farmer group Harapan Maju CF in the Mobui Village, Kembayan District, Sanggau Regency, West Kalimantan. Data were collected through interviews with the management of the joint business group (KUB) of Mobui Majua covering fixed and variable costs based on market prices. In this research, some assumptions that are in line with field conditions are used for financial and sustainability analysis of POC production. The result shows that the activity of making POC by Mobui Majua CF is financially feasible with a positive Net Present Value (NPV), Benefit Cost Ratio (BCR) of 1.56, Return on Investment (ROI) of 55.67%, and Payback Period (PP) in 7.5 months. Human resources skill and capability, proper marketing strategy, effective institution and raw material supply certainty are influencing factors for the POC business sustainability